Elevational patterns of soil nematode diversity, community structure and metabolic footprint in the Trikuta mountains of Northwestern Himalaya - Choudhary, Fozia; Bhardwaj, Anil; Sayeed, Iqra; Rather, Shabir Ahmad; Khan, Mohammad Abdul Hannan; Shah, Ali Asghar (Frontiers in Forests and Global Change, 2023)
Nematodes are an integral part of soil biodiversity and play a vital role in soil nutrient cycling. The Himalayan mountainous ecosystems are amongst the extreme environments in the world. Still little is known about the diversity and distribution patterns of soil nematodes along the elevation gradient in the region, thus limiting our ability in understanding and comparing the structural patterns of nematode communities across different regions. To address this knowledge gap, we aim to disentangle the elevational patterns of soil nematode community structure and trophic diversity by studying the abundance, composition, diversity and functional indices, and metabolic footprint of soil nematodes at four elevation classes (Elev1, Elev2, Elev3, and Elev4 each being 400 m) along an altitudinal gradient (1,000–2,600 m) in the Trikuta mountain range of Pir-Panjal to Shivalik Himalaya. Overall, a total of 55 genera were found in the study region. The diversity and richness of soil nematodes varied significantly among the elevation classes, and exhibit a decreasing trend with elevation. Also, the nematode community composition varied significantly among the elevation classes along the elevational gradient. The bacterivores were the dominant trophic group at each elevation class. Further, the soil properties played a key role in explaining the changes in the nematode community composition across the elevation classes. Moreover, the total nematode, bacterivore and herbivore abundances showed an increasing trend, while as that of fungivores and predators exhibit a negative trend with elevation. In addition, a declining pattern in the overall maturity and metabolic footprint with elevation was observed, thus depicting the lower sustenance of k-strategic nematodes and their relatively lower contribution to belowground carbon cycling at higher elevations. The finding of our study could enhance our understanding of the overall community structure and diversity patterns of soil nematode along the elevation gradient, and the response of soil nematodes to ongoing climate change in the rapidly warming Himalayas.